2017
DOI: 10.17235/reed.2017.4520/2016
|View full text |Cite
|
Sign up to set email alerts
|

Appendicopathy. A report of eight cases

Abstract: Neurogenic appendicopathy is an uncommon entity that can evolve as abdominal pain which is similar to acute appendix. Simple appendectomy is curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The incidence of appendicitis obliterans ranges between 0.16% to 0.81% in adult population as per different studies [4,5] while incidence in paediatric population is about 0.25%. The disorder is more common in second decade of life rather than first decade and is more common in female population [6].…”
Section: What Is the Incidence Of Appendicitis Fibrous Obliterans?mentioning
confidence: 93%
See 1 more Smart Citation
“…The incidence of appendicitis obliterans ranges between 0.16% to 0.81% in adult population as per different studies [4,5] while incidence in paediatric population is about 0.25%. The disorder is more common in second decade of life rather than first decade and is more common in female population [6].…”
Section: What Is the Incidence Of Appendicitis Fibrous Obliterans?mentioning
confidence: 93%
“…A study that identified an incidence of 0.16% of neurogenic appendicopathy followed up all patients for a mean period of 73.2 ± 28 months concluded that all patients who underwent remained asymptomatic [5].…”
Section: What Is Appendicitis Fibrous Obliterans?mentioning
confidence: 99%
“…The term “chronic appendicitis” is one of several terminologies used to describe cases of NA with fibrosis, but lacking an acute inflammatory reaction. NA represents from 0.16% [ 8 ] to17.1% of all cases of surgically treated appendicitis [ 5 , 9 , 10 ]. It is more common in females than in males.…”
Section: Introductionmentioning
confidence: 99%
“…It is more common in females than in males. It is common in the third decade (27.8 ± 12 years) of life [ 8 ], and after 45 years of age, but uncommon in the first decade of life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appendiceal neuroma consist of a proliferation of fusiform cells in a myxoid background comprising of connective tissue, fatty tissue and eosinophils. These fusiform cells are positive 14,15,16,17 for S-100 protein and neuron-specic enolase.…”
mentioning
confidence: 98%